The Structure of Technology Over Time: A Model for Testing the "Putty-Clay" Hypothesis - Fuss, Melvyn A. (Econometrica, 1977)
This paper develops an econometric model of production technology in terms of the ante-ex description of production possibilities. Ex ante and ex post substitution characteristics are allowed to differ from one another and parametric representations are derived which provide arbitrary second-order approximations to the true underlying characteristics. Nested in the maintained model are the specialized putty-putty, puttyclay, and structures of technology; and hypothesis tests are developed to test for the applicability of these specialized structures. An example is provided in which the hypotheses that fossil fuel electricity generation can be characterized by putty-clay or clay-clay technologies are tested using data drawn from individual United States electricity generating plants.